Efficacy of Isatuximab With Pomalidomide and Dexamethasone in Relapsed Myeloma: Results of a UK-Wide Real-World Dataset. Issue 6 (26th June 2022) - Djebbari, Faouzi; Rampotas, Alexandros; Vallance, Grant; Panitsas, Fotios; Basker, Nanda; Sangha, Gina; Salhan, Beena; Karim, Farheen; Al-Kaisi, Firas; Gudger, Amy; Ngu, Loretta; Poynton, Matt; et al.
Abstract : Real-world data on the efficacy and tolerability of isatuximab with pomalidomide and dexamethasone (IsaPomDex) in relapsed/refractory myeloma patients have not been reported. In this UK-wide retrospective study, IsaPomDex outcomes were evaluated across 24 routine care cancer centers. The primary endpoint was overall response rate (ORR). Secondary endpoints included progression-free survival (PFS), duration of response (DOR) for patients who achieved an objective response (≥partial response [PR]), and adverse events (AEs). In a total cohort 107 patients, median follow up (interquartile range [IQR]) was 12.1 months (10.1–18.6 mo), median age (IQR) was 69 years (61–77). Median (IQR) Charlson Comorbidity Index (CCI) score was 3 (2–4); 43% had eGFR <60 mL/min. Median (IQR) number of prior therapies was 3 (3–3). Median (IQR) number of IsaPomDex cycles administered was 7 (3–13). ORR was 66.4%, with responses categorized as ≥ very good partial response: 31.8%, PR: 34.6%, stable disease: 15.9%, progressive disease: 15%, and unknown 2.8%. Median PFS was 10.9 months. Median DOR was 10.3 months. There was no statistical difference in median PFS by age (<65: 10.2 versus 65–74 13.2 versus ≥75: 8.5 mo, log-rank P = 0.4157), by CCI score (<4: 10.2 mo versus ≥4: 13.2, log-rank P = 0.6531), but inferior PFS was observed with renal impairment (≥60: 13.2 versus <60: 7.9 mo, log-rank P = 0.0408). Median OS was 18.8 months. After a median of 4 cycles, any grade AEs were experienced by 87.9% of patients. The most common ≥G3 AEs were neutropenia (45.8%), infections (18.7%), and thrombocytopenia (14%). Our UK-wide IsaPomDex study demonstrated encouraging efficacy outcomes in the real world, comparable to ICARIA-MM trial.